2010
DOI: 10.1146/annurev.nutr.012809.104701
|View full text |Cite
|
Sign up to set email alerts
|

The Endocannabinoid System and Its Relevance for Nutrition

Abstract: Endocannabinoids bind to cannabinoid, vanilloid, and peroxisome proliferator-activated receptors. The biological actions of these polyunsaturated lipids are controlled by key agents responsible for their synthesis, transport and degradation, which together form an endocannabinoid system (ECS). In the past few years, evidence has been accumulated for a role of the ECS in regulating food intake and energy balance, both centrally and peripherally. In addition, up-regulation of the ECS in the gastrointestinal trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 96 publications
1
125
0
1
Order By: Relevance
“…Moreover, these genotypes were associated with increased basal levels of multiple GPCRs, including CB1R and dopamine receptor D2 (DRD2) [7]. In line with the notion that increased CB1R signaling accrues food intake and hence favors obesity and insulin resistance, while pharmacological or genetic CB1R inhibition has opposite effects [9], Becn2 +/− mice accumulated more weight than their wild-type littermates in response to a standard (as well as to a high-fat) diet. At odds with their Becn1 +/− counterparts, Becn2 +/− mice also exhibited impaired glucose tolerance and decreased insulin sensitivity, two effects that could be reverted by a chemical CB1R antagonist [7].…”
Section: Becn2mentioning
confidence: 67%
“…Moreover, these genotypes were associated with increased basal levels of multiple GPCRs, including CB1R and dopamine receptor D2 (DRD2) [7]. In line with the notion that increased CB1R signaling accrues food intake and hence favors obesity and insulin resistance, while pharmacological or genetic CB1R inhibition has opposite effects [9], Becn2 +/− mice accumulated more weight than their wild-type littermates in response to a standard (as well as to a high-fat) diet. At odds with their Becn1 +/− counterparts, Becn2 +/− mice also exhibited impaired glucose tolerance and decreased insulin sensitivity, two effects that could be reverted by a chemical CB1R antagonist [7].…”
Section: Becn2mentioning
confidence: 67%
“…Other studies have shown an increased formation of DHEA and EPEA in various tissues, including prostate and breast cancer cells, after administering fish oil or individual n-3 long-chain PUFA (19,20) . Interestingly, we have also reported evidence that both DHEA and EPEA show greater anti-proliferative effects than their parent compounds, DHA and EPA, in two prostate cancer cell lines, LNCaP and PC3 cells (15) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 92%
“…All stimuli involved in feeding are centrally integrated by the hypothalamus, a brain area known to play an important role in homoeostatic control, thus maintaining an adequate body weight (19) . There is now convincing evidence that the endocannabinoid system is involved in the regulation of food intake and energy expenditure.…”
Section: Endocannabinoids In the Control Of Food Intake And Energy Exmentioning
confidence: 99%
“…[1][2][3][4] As endocannabinoids (ECs) are produced on demand in specific tissues, 5 what is measured in the circulation is probably spillover of unknown origin. Previous studies indicate a dysregulation of the ECS in human obesity with differentially regulated levels in various AT depots.…”
Section: Introductionmentioning
confidence: 99%
“…14 The ECs function mainly as neurotransmitters, and because of their highly lipophilic nature, they cannot be stored in vesicles and have to be produced on demand. 5 2-AG is synthesised by diacylglycerol lipase and degraded by monoglyceride lipase (MGL), 15 whereas AEA can be produced by N-acyl phosphatidylethanolamine-specific phospholipase D (NAPE-PLD) and degraded by fatty acid amide hydrolase (FAAH). 16 Several forms of this enzyme exist, both FAAH2 and N-acylethanolamine-hydrolysing acid amidase but their roles are less characterised.…”
Section: Introductionmentioning
confidence: 99%